Senegalese Stagecraft : Decolonizing Theater-Making in Francophone Africa - Valente-Quinn, Brian (Book collections on Project MUSE., 2021)
"Senegalese Stagecraft explores the particular role of the theatrical stage in Senegal as a site of poetic expression, political activism, and community engagement"--